Effects of Energy Prices on Food Consumer Price Inflation - Richhild Moessner (CESifo GmbH, 2025)
This paper studies the effects of country-specific energy prices on food consumer price inflation (CPI) within a cross-country Phillips curve framework. It considers a panel of 36 OECD member and candidate economies using quarterly data from the start of 1994 to the end of 2021. We find that energy CPI inflation has a significantly positive effect on food CPI inflation, after controlling for the output gap, exchange rate changes and global factors. This result is generally robust to also controlling for inflation expectations, global food commodity prices and core CPI inflation. We also find that the effect of energy CPI inflation on food CPI inflation is significantly larger when energy dependency is higher.
Keywords: E31; E52; E58; 330; inflation; food prices; energy prices